Evaluating Readiness in Using Mobile devices for Educational Purposes among Educators and Students - Khan, M. M. H; R., Jeyagopi (INTI International University, 2019)
Mobile technology is providing a new frontier for the application of educational technology within the academia. However, as with any relatively new technology, much has to be understood before it can be employed effectively. One of the most logical early steps is to understand the perception of lecturers and the students. This paper presents the results of a survey at INTI International University, Malaysia. The findings will help in formulating a well-planned and user-centric approach on application of mobile technology. The respondents also indicated a favorable perception of m-learning although 64% of them have never used it. The majority (76.5%) of responders also believes that m-learning would be useful for their students, and 86.4%of responders were agreed to attempt to tap on the potential of using the networks and smartphones for educational purposes. The survey was also carried out on 85 engineering students (both Degree and Diploma level) through questionnaire at INTI International University, Malaysia. The result showed the positive potentials and capabilities of the smart phones used in the engineering education. This indicates that engineering education could advantage from utilizing these new technological tools.